Muttaqin Tujuan Akhir Pendidikan Manusia (Kajian Pedagogis) - Syamsyurizal Yazid; Luthfi Anis Muadzin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to describe the role of the concept of taqwa in Islamic education as a moral guide to achieve the ultimate goal of human education. Taqwa, as one of the core concepts in Islam, has a profound meaning and is very influential in shaping the character of individuals who believe and are responsible in the life of this world and the hereafter. Islamic education seeks to form human beings who are not only intellectually intelligent, but also have high spiritual awareness. The concept of taqwa in Islamic education integrates spiritual, moral, and intellectual aspects that include practicing the teachings of Allah in daily life, social interaction, and achieving balanced life goals between this world and the hereafter. This study uses a library research method by analyzing various literature related to taqwa in the perspective of Islamic education, including interpretation of the Qur'an, hadith, and Islamic education books. The results of the study show that the application of taqwa values in education is expected to form a generation that is not only successful in this world, but also survived in the hereafter. Therefore, Islamic education based on the concept of taqwa aims to create individuals who have a balance between worldly intelligence and spiritual depth, so that they can achieve worldly happiness and salvation in the hereafter.